2020
DOI: 10.1029/2019jb018631
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of Paleocene‐Maastrichtian (60–70 Ma) Lava Flows From Tian Shan (Central Asia): Directional Analysis and Paleointensities

Abstract: The Tuoyun volcanics from the Tian Shan range (Central Asia) give an opportunity to investigate the variability of the Earth's magnetic field during the Cretaceous and Early Paleogene. In the paper we focus on Maastrichtian-Paleocene basalts and report new paleomagnetic results from 70 lava flows (respectively 45 directional groups) sampled near Tuoyun village (75.33°E; 40.18°N) from three distinct sections. Combined with previous results, our new data set yields a virtual geomagnetic pole at φ S ¼ 180.2°E, ϑ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 107 publications
(251 reference statements)
0
8
0
Order By: Relevance
“…For instance, the APWP for Asia (Cogné et al, 2013) suggests a more southerly position for Asia at ∼50 Ma which theoretically requires a southward shift of Asia during the Cretaceous and Early Paleogene. Moreover, Meng et al (2020) reported a paleomagnetic pole from the latest Cretaceous and Paleocene (∼70-60 Ma) volcanics from the Tuoyun Basin at the northern margin of the Tibetan Plateau that yielded a paleolatitude of 21.3° ± 3.8° N (Site location at 40.2°N, 75.3°E). The observed paleolatitude is much lower than that calculated from the APWP of Eurasia (38.8° ± 3.0° N, Torsvik et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the APWP for Asia (Cogné et al, 2013) suggests a more southerly position for Asia at ∼50 Ma which theoretically requires a southward shift of Asia during the Cretaceous and Early Paleogene. Moreover, Meng et al (2020) reported a paleomagnetic pole from the latest Cretaceous and Paleocene (∼70-60 Ma) volcanics from the Tuoyun Basin at the northern margin of the Tibetan Plateau that yielded a paleolatitude of 21.3° ± 3.8° N (Site location at 40.2°N, 75.3°E). The observed paleolatitude is much lower than that calculated from the APWP of Eurasia (38.8° ± 3.0° N, Torsvik et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our updated paleomagnetic pole fully supports the initial collision model proposed by Yi et al (2011) and confirms an initial contact between India and Asia by ∼61 Ma at ∼7°N (Figure 4). Using our updated Dianzhong pole (∼64-60 Ma) and the Tuoyun pole (∼70-60 Ma) from Meng et al (2020) yields a latitudinal crustal shortening of 5.3° ± 4.3° (∼600 ± 480 km) that is consistent with estimates based on structural geology (Li et al, 2015;van Hinsbergen et al, 2011). It is difficult to decipher the overall shortening budget in the Asian interior as the motion of stable Asia needs refinement given the complexities suggested in this and other studies (e.g., Cogné et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the paleolatitudinal comparison based on reliable This is a provisional file, not the final typeset article paleomagnetic poles, paleomagnetism provides a direct constrain on timing and locus for the initial collision between India and Asia (e.g., Dupont-Nivet et al, 2010;Najman et al, 2010;Yi et al, 2011Yi et al, , 2021 The Indian plate was subjected to rapid northward motion toward Asia during the Cretaceous and Paleocene (Patriat and Achache, 1984;Yin and Harrison, 2000;van Hinsbergen et al, 2011). The kinematics of the northern margin of India can be constrained by the Cretaceous and Paleogene paleomagnetic data obtained from the Tethyan Himalaya (Besse et al, 1984;Patzelt et al, 1996;Tong et al, 2008;Yi et al, 2011;Yang et al, 2015Yang et al, , 2019Ma et al, 2016;Meng et al, 2019Meng et al, , 2020Y. Zhang et al, 2019;Yuan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Indian plate was subjected to rapid northward motion toward Asia during the Cretaceous and Paleocene (Patriat and Achache, 1984;Yin and Harrison, 2000;van Hinsbergen et al, 2011). The kinematics of the northern margin of India can be constrained by the Cretaceous and Paleogene paleomagnetic data obtained from the Tethyan Himalaya (Besse et al, 1984;Patzelt et al, 1996;Tong et al, 2008;Yi et al, 2011;Yang et al, 2015;Ma et al, 2016;Yang et al, 2019;Meng et al, 2019;Meng et al, 2020;Yuan et al, 2020). For the lack of contemporary volcanic rocks, the Late Cretaceous to Paleocene sedimentary rocks from the Tethyan Himalaya are especially crucial for reconstructing the overall process of the India-Asia collision.…”
Section: Introductionmentioning
confidence: 99%